Gimik the reunion - Dyogi, Laurenti; Star Cinema Production (Firm). (Quezon City Star Cinema, 2004)
Months after they graduated from college, the relationship within the barkada start to change. With new priorities in their personal lives and unresolved issues with each other from the past, they are led to take separate paths.
VCD
Stroy & screenplay Marcia De Jesus, Keiko Aquino, line producer Ariel R.Salumbides, executive producer Charo Santos-Concio ; directed by Laurenti M. Dyogi
Rico Yan, Giselle Toengi, Diether Ocampo, Mylene Dizon
Keywords: Feature films